The Evaluating the relationship between high blood pressure and menstrual irregularities among Ahmadu bello university students, Nigeria - Iorhemen, Raymond T.; Ochube, Godwin A.; Ugbong, Paul U.; Akpa, Roseline E. (International Journal of Health, 2024)
Purpose: Menstruation is a part of the changes in the function of the ovaries in women that occurs in women of childbearing age. High blood pressure is defined for a systolic blood pressure (sBP) of 90 mmHg and a diastolic blood pressure (dBP) of 140 mmHg. This research establishes the relationship between menstruation and high blood pressure among university athletes of menstruating age. Methods: Ten volunteer university athletes were used for this study. The ages, height and weight of the subjects were measures. Also, the blood pressure (systolic and diastolic) and heart rates were measured before, during and after the exercise at menstruation period and also at seven days after menstruation. Results: Results show the following; average age and height of the subjects were 25.5 years and 178 cm, weight increased significantly (at 95 % confidence level) during menstruation from 57.54 Kg to 58.35 Kg. sBP during menstruation was 121 mmHg while dBP was 66 mmHg. After menstruation, sBP gave 117 mmHg and dBP gave 44 mmHg. Resting heart rate was 70.1 bpm at the start of the menstruation, and 74.2 bpm after menstruation. For the recovery heart rate, 96.12 bpm was recorded at menstruation, while 97.9 bpm was recorded after menstruation. Conclusion: This study infers that there is a significant difference between these activities at first day of menstruation and seven days after menstruation. The chief reason for this is the hormonal disorder that occurs during menstruation.